2008
DOI: 10.1017/s1035077200000080
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers' understanding of child abuse and their professional role in child protection

Abstract: Universities play an integral role in training teachers in the areas of understanding and preparedness to deal with child abuse and neglect while at the same time advocating for the ‘rights of the child’. Unfortunately pre-service teachers are at risk of being ill-prepared to meet their mandated and teaching responsibilities if their course content is not approached strategically. While numerous studies have investigated teachers' understandings of child abuse and the barriers in detecting and reporting this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The call to develop pre-service pastoral training for recognising and reporting child abuse and neglect (see UNESCO, 2009;Wurtele, 2009) is now almost deafening, and covers all levels of pre-service teacher education, for example, for early childhood (Fenton, 2008), primary school (Brown, 2008;Goldman & Bradley, 2011) and secondary school (Goldman & Collier-Harris, 2012). Briggs (2006) argues that education authorities should require student-teachers to complete a university course in identification and reporting of child abuse before they are allowed to undertake fieldwork, that is in practice teaching (or practicum).…”
Section: Child Sexual Abusementioning
confidence: 99%
See 2 more Smart Citations
“…The call to develop pre-service pastoral training for recognising and reporting child abuse and neglect (see UNESCO, 2009;Wurtele, 2009) is now almost deafening, and covers all levels of pre-service teacher education, for example, for early childhood (Fenton, 2008), primary school (Brown, 2008;Goldman & Bradley, 2011) and secondary school (Goldman & Collier-Harris, 2012). Briggs (2006) argues that education authorities should require student-teachers to complete a university course in identification and reporting of child abuse before they are allowed to undertake fieldwork, that is in practice teaching (or practicum).…”
Section: Child Sexual Abusementioning
confidence: 99%
“…Student-teachers found that the integration and application of theoretical knowledge into real-world issues was valuable (2008). Similarly, student-teachers in Brown's (2008) Queensland study of pre-service primary and early childhood education made suggestions on course structure, such as 'providing seminars, workshops and information sessions, creating a new and separate course, and integrating content and procedures into professional experience courses' (p. 30). Crucially, some of these student-teachers recognised that changes to course structure and/or content need to be compulsory (Brown, 2008).…”
Section: Courses For Child Sexual Abuse and Mandatory Reporting In Tementioning
confidence: 99%
See 1 more Smart Citation
“…Research in this area, although relatively recent and scant, has consistently shown that student teachers feel ill-equipped to deal with child protection matters (Briggs & Hawkins, 1997;Brown, 2008;Goldman, 2007;Goldman & Grimbeek, 2008); they are concerned about interagency cooperation with maltreating families (Bishop, Lunn & Johnson, 2002), and are apprehensive both about how to respond to student disclosures (David, 1993;Rossato & Brackenridge, 2009) and how to report suspected cases (McKee & Dillenburger, 2010;Watts & Laskey, 1994).…”
Section: Child Protection and Preservice Teachersmentioning
confidence: 99%
“…Goldman's (2007) study of Queensland preservice teachers found low levels of confidence in their ability to accurately identify and effectively respond to child maltreatment. Similarly, Brown's (2008) study of Queensland preservice teachers found low levels of awareness of maltreatment subtypes and indicators as well as inadequate understanding of their professional reporting obligations. McKee and Dillenburger's (2010) study of Irish student teachers found considerable gaps in their knowledge of child maltreatment prevalence, warning signs and indicators, reporting processes, policies and legislative frameworks and day-to-day working with children experiencing maltreatment.…”
Section: Child Protection and Preservice Teachersmentioning
confidence: 99%